2013
DOI: 10.1177/0018720813495280
|View full text |Cite
|
Sign up to set email alerts
|

Driving With the Wandering Mind

Abstract: The results suggest that situations that are likely associated with mind-wandering (e.g., route familiarity) can impair driving performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(58 citation statements)
references
References 22 publications
0
57
1
Order By: Relevance
“…Failure to become aware of one’s surroundings in these instances may represent an instance of mind-wandering while walking. The people may have become focused on their own thoughts and been less aware of their surroundings (He et al, 2011; Yanko and Spalek, 2013, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to become aware of one’s surroundings in these instances may represent an instance of mind-wandering while walking. The people may have become focused on their own thoughts and been less aware of their surroundings (He et al, 2011; Yanko and Spalek, 2013, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…For example, Yanko and Spalek (2014) found that people sometimes lose awareness while driving in a simulator. When probed, participants acknowledged occasions of mind-wandering; that is thinking about something other than the task of driving (see also He et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cheyne et al (2009) proved the robustness of the coefficient of variability—on a given interval, mean reaction time divided by its variability—to study MW in details (Bastian and Sackur, 2013; Esterman et al, 2013). Parallel to those results, subject accuracy is extensively used, whether it during trial to trial tasks (Braem et al, 2015; Durantin et al, 2015; Konishi et al, 2015) or during continuous monitoring, such as in a car simulator (He et al, 2011; Cowley, 2013; Yanko and Spalek, 2014). On the whole, behavioral markers can highlight performance decrements induced by MW in many different tasks.…”
Section: Mw Markers To Study Ootlmentioning
confidence: 99%
“…In brain imaging studies, MW is characterized by the activation of the Default Mode Network, a widely distributed brain region comprised of medial prefrontal cortex and the posterior cingulate cortex (Mason et al, 2007; Christoff et al, 2009; Christoff, 2012; Konishi et al, 2015). Even though MW is thought to facilitate prospection, introspection and problem solving (Smallwood and Schooler, 2006), performance drops in numerous tasks has been observed during MW episodes (He et al, 2011; Galera et al, 2012; Schad et al, 2012; Bastian and Sackur, 2013; Casner and Schooler, 2013, 2015; Yanko and Spalek, 2014; Berthié et al, 2015). Several aspects outline a possible role of MW in OOTL in highly reliable automated environments.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that such strong endorsements from leading researchers in the field are likely to result in a surge of research activity building on Axelrod et al (2015)'s result. From a more applied perspective, mind wandering has been, for example, associated with accidents in car driving (He, Becic, Lee, & McCarley, 2011;Yanko & Spalek, 2014) and aviation (Wiegmann et al, 2005), and a technique that consistently and reliably allows to manipulate the propensity to mind-wander has thus great potential to avoid many of these human errors. Furthermore, ruminations, which may be seen as a special case of mind wandering, are core features of clinical conditions such as major depression or obsessivecompulsive disorder.…”
Section: Introductionmentioning
confidence: 99%